Pricing Consistency in Coffee Business Management: A Comprehensive Study - Maspul, Kurniawan Arif (Journal Arbitrase : Economy, Management and Accounting, 2024)
The study presents a comprehensive analysis of pricing consistency in coffee business management, recognizing its critical role in ensuring trust, dependability, and sustainability in a competitive market. Through theoretical frameworks like transaction cost economics, agency theory, and signaling theory, the study explores how pricing uniformity enhances transactional efficiency, aligns incentives between management and stakeholders, and communicates quality to customers. Challenges in maintaining pricing consistency are discussed, highlighting the implications for business sustainability, internal dynamics, and social responsibility. The method involves a qualitative examination of pricing practices in Al Qassim's coffee value chain, integrating observational analysis, interviews with coffee shop owners, and literature review to uncover insights and potential solutions. By understanding pricing consistency, coffee businesses can foster consumer trust, improve operational efficiency, and navigate long-term success in a dynamic economy.